Pengaruh derajat laserasi perineum terhadap skala nyeri perineum pada ibu post partum - Istiana, Siti; Rahmawati, Agustin; Kusumawati, Erna (Jurnal Kebidanan, 2020)
Lacerations of the birth canal in addition to the weight factor of the baby and the type of delivery, the factor of the perineum/legs of the perineum is especially influential. Perineal injuries are usually very painful by the puerperal mother but apparently, some puerperal mothers do not feel pain even though there is a laceration in the perineum. This happens because the pain for each person is different. The purpose of this study was to determine the effect of the degree of laceration with perineal pain in postpartum mothers at the Bandarhardjo Public Health Center in Semarang City. This type of research is analytic, the sample in this study is postpartum mothers who have perineal laceration but there are no complications of 30 people. The research instrument uses a questionnaire. The results showed the majority of respondents experienced a degree 2 perineal laceration, the majority of respondents experienced a mild pain scale (rating scale 3) and there was an influence of the degree of tear perineum on the perineal pain scale.